211k views
0 votes
The function f(x) =2(3)^x is to be multiplied by the function g(x) 3(3)^(2x) to create the function h(x). Which function is produced?

A. h(x)=6(9)^(3x)

B. h(x)=6(3)^(2x^2)

C. h(x)=6(3)^(3x)

D. h(x)=6(6)^(2x^2)
Please show work!

1 Answer

7 votes

Answer C is the right answer.

Explanation:

h(x) = f(x) * g(x)

h(x) = (2*3^x ) * ( 3*3^2x )

2 * 3 is easy, that will be 6.

The ground number 3 remains 3 in h(x), so that is easy too...

But with multiplying exponents, you can add them.

Let's concentrate only on the exponents of f(x) and g(x)... and add them...

x + 2x =3x

So, now combine the easy part with this new exponent, and you get h(x) = 6*(3)^(3x)

So answer C is the right answer.

User Gavioto
by
5.6k points